Approach of the systems to evaluation of risks at planning of industrial objects - Статюха, Геннадій Олексійович; Бойко, Тетяна Владиславівна; Абрамова, Алла Олександрівна (Eastern-European Journal of Enterprise Technologies, 2012)
The questions of evaluation of designed risks of industrial objects are investigational. Approach of the systems is offered to the evaluation of designed risks of industrial objects. The mathematical model of evaluation of designed risks of industrial objects is developed